Suicide-associated comorbidity among US males and females: a multiple cause-of-death analysis. Issue 5 (4th October 2007) - Rockett, Ian R H; Wang, Shuhui; Lian, Yinjuan; Stack, Steven
Abstract : Objective: To describe physical and mental comorbidity among male and female suicides in the US. This research replicates a seminal Australian study, which permits inference on comparative cause-of-death data quality. Design and setting: National cross-sectional study of suicides and unintentional injury decedents (comparison group) using Multiple Cause of Death (MCOD) public use files for 1999–2003. Main outcome measures: Prevalence of medical conditions; relative odds of suicide-associated comorbidity. Results: For 14% of male suicides and 19% of female suicides, comorbidity was shown on their death certificates. Respective prevalences for mental and physical comorbidity were 7.2% and 7.1% for males and 10.0% and 9.3% for females. Mean numbers of psychopathologies mentioned were virtually identical for male and female suicides (1.22 and 1.21) for whom comorbidity was registered. Mean mentions of physical disease were lower for male suicides: 1.64 vs 1.77. Multiple medical conditions were registered for 4% of male suicides and 6% of female suicides. Suicides manifested excess comorbidity for depression and mood disorders (adjusted odds ratio (AOR) = 34.6, 95% CI = 32.41 to 36.92), schizophrenia (AOR = 2.5, 95% CI = 2.16 to 2.88), and cancer (AOR = 2.1, 95% CI = 1.93 to 2.19), but unexpectedly no excess comorbidity for HIV. Conclusions: The US system of death certification appears to be less fastidious than the Australian system. Although comorbidity patterns were very similar, only half as much psychopathology was reported for US suicides as for Australian suicides. A questionable deficit of comorbid physical disease was also documented for US suicides. Findings have important implications for medical training, as well as for suicide surveillance, policy, and prevention.